2005
DOI: 10.1128/mcb.25.2.716-727.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of the Tup11 and Tup12 Transcriptional Corepressors in Fission Yeast

Abstract: Gene duplication is considered an important evolutionary mechanism. Unlike many characterized species, the fission yeast ؊ mutants and are over-represented in genes that have previously been shown to respond to a range of different stress conditions. Genes specifically derepressed in tup12 ؊ mutants require the Ssn6 protein for their repression. As for Tup12, Ssn6 is also required for efficient adaptation to KCl-and CaCl 2 -mediated stress. We conclude that Tup11 and Tup12 are at least partly functionally dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…The individual genes identified in each of these experiments are listed in Table S1 in the supplemental material. Several genes showing altered expression in each of these DNA microarray studies have been studied independently by RT-PCR under the same conditions (data not shown) (13). In general, the results were in good agreement with the DNA microarray results.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The individual genes identified in each of these experiments are listed in Table S1 in the supplemental material. Several genes showing altered expression in each of these DNA microarray studies have been studied independently by RT-PCR under the same conditions (data not shown) (13). In general, the results were in good agreement with the DNA microarray results.…”
Section: Resultssupporting
confidence: 77%
“…1A), similar to that observed for Tup11 and Tup12 previously (13). To analyze the function of Ssn6, we created a diploid strain containing a heterozygous null allele of the ssn6 gene by insertion of a kanamycin cassette.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular and biochemical studies document that a Tup1p has three functionally defined domains: an N-terminal domain involved in interactions with Ssn6p (Carrico and Zitomer, 1998;Zhang et al, 2002), a C-terminal seven repeated WD40 domain important for protein interactions and tetramerization (Sprague et al, 2000), and a central domain required for the repression activity of the complex (FagerstromBillai and Wright, 2005;Tzamarias and Struhl, 1994). In spite of their similar structures, repressions of target genes by Tup1 proteins are reported to occur by different molecular mechanisms (Fagerstrom-Billai and Wright, 2005).…”
Section: Introductionmentioning
confidence: 99%